Things I never told you - Vogt, Beth K. (Vogt, Beth K. Thatcher sisters, 2018)
It's been ten years since Payton Thatcher's twin sister died in an accident. Payton has reinvented herself as a partner in a successful party-planning business and is doing just fine-- as long as she manages to hold her memories and her family at arm's length. With her middle sister Jillian's engagement, Payton's party-planning skills are called into action, which means working alongside her opinionated oldest sister, Johanna. When a frightening diagnosis threatens Jillian's future, old wounds are reopened and the family faces the possibility of another tragedy. Will they pull together or be driven further apart?